METACOGNITIVE STRATEGIES OF GOOD READERS IN READING RECOUNT TEXT FOR THE EIGHTH GRADERS OF JUNIOR HIGH SCHOOL (RETAIN, 2017)
METACOGNITIVE STRATEGIES OF GOOD READERS IN READING RECOUNT TEXT FOR THE EIGHTH GRADERS OF JUNIOR HIGH SCHOOL Ika Fitri Andriani English Education Department, Faculty of Languages and Arts, State University of Surabaya ikapit96@gmail.com Fahri, M.A. English Education Department, Faculty of Languages and Arts, State University of Surabaya fahri@unesa.ac.id Abstrak Kurang membaca merupakan permasalahan paling umum dalam sistem pendidikan. Masalah ini disebabkan oleh dua hal. Pertama, siswa kehilangan motivasi untuk membaca sebuah teks. Kedua yaitu teks yang sulit untuk dipahami, terutama teks bertulisan Bahasa Inggris. Maka, dibutuhkan strategi yang baik untuk mendorong motivasi membaca dan pemahaman bacaan pada siswa. Ada beberapa control tujuan membaca dan aktivitas membaca yang bisa membantu siswa untuk memahami teks, berikut dengan tiga proses dari strategi metakogntinif. Penelitian ini dilakukan pada siswa Sekolah Menengah Pertama kelas 8. Deskriptif kualitatif merupakan metode penelitian yang digunakan untuk memperoleh deskripsi detail terkait penggunaan strategi metakognitif pada pembaca kompeten. Observasi difokuskan pada cara siswa menggunakan tiga proses dari strategi metakognitif seperti perencanaan, monitor, dan evaluasi. Data diperoleh dari jurnal siswa yang ditulis seusai pelajaran. Menurut perolehan data, pembaca kompeten dari Sekolah Menengah Pertama (SMP) menunjukkan bahwa mereka memanfaatkan penggunaan strategi metakognitif dengan sesuai. Mereka mencoba berbagai aktivitas membaca yang berbeda untuk mencapai tujuan membaca dan memahami isi teks bacaan lebih baik. Akhirnya, hampir keseluruhan dari mereka berhasil memahami isi teks bacaan dan mencapai tujuan membaca yang sudah mereka rencanakan sebelumnya. Kata Kunci: strategi membaca, strategi metakognitif, strategi perencanaan, strategi monitor, strategi evaluasi, jurnal siswa.baca Abstract Lack of reading is the most common problem in education system. Actually, there are two main causes. First, the students lose their motivation to read a text. Second, the text is difficult to comprehend, especially the English-written text. Then, good strategy is needed to encourage students’ reading motivation and reading comprehension. Metacognitive strategy is a strategy that claimed as the suitable strategy for reading comprehension. There are many control reading goals and activities that can help students to comprehend the text, following the three processes of metacognitive strategies. This study was conducted to the eighth graders of Junior High School. Descriptive qualitative was the research design that used in order to get detailed description about the use of metacognitive strategy of good readers. The observation focused on the way how the students use the three processes of metacognitive strategy such as planning, monitoring, and evaluating processes. The data were gained from learning logs that students wrote after the lesson. According to the data, good readers of Junior High School students showed that they utilized the metacognitive strategy properly. They attempted different reading activities in order to reach the reading goals and comprehend the text better. Finally, most of them succeeded in comprehends the text and reach the reading goals that they planned before. Keywords: Reading, Strategy, Metacognitive Strategies, Planning Strategy, Monitoring Strategy, Evaluating Strategy, Learning Logs.